Artificial Cellulosome Complex from the Self‐Assembly of Ni‐NTA‐Functionalized Polymeric Micelles and Cellulases. (15th April 2019) - Lu, Lin; Zhang, Libo; Yuan, Liang; Zhu, Tianyu; Chen, Wilfred; Wang, Guiren; Wang, Qian
Abstract: Polymer–protein core–shell nanoparticles have been explored for enzyme immobilization. This work reports on the development of functional polymeric micelles for immobilizing His6 ‐tagged cellulases with controlled spatial orientation of enzymes, resulting in "artificial cellulosomes" for effective cellulose hydrolysis. Poly(styrene)‐ b ‐poly(styrene‐ alt ‐maleic anhydride) was prepared through one‐pot reversible addition–fragmentation chain‐transfer polymerization and modified with nitrilotriacetic acid (NTA) to afford an amphiphilic block copolymer. The self‐assembled polymer was mixed with a solution of NiSO4 to form Ni‐NTA‐functionalized micelles, which could successfully capture His6 ‐tagged cellulases and form hierarchically structured core–shell nanoparticles with cellulases as the corona. Because the anchored enzymes are site‐specifically oriented and in close proximity, synergistic catalysis that results in over twofold activity enhancement has been achieved. Abstract : Caught in a bind : Site‐specific recognition units have been designed on the surface of polymeric nanoparticles to capture proteins with controlled spatial orientation. The captured proteins are within close proximity, as demonstrated by FRET effect. Close proximity also promotes synergistic catalysis, and over twofold catalytic activity enhancement is observed for the assembled cellulases, compared with that of their free counterparts.